Analysis of the phytochemical composition and assay of total flavonoids of the hydroalcohol extracts of Cyperus iria L. and Cyperus articulatus L. / Análise da composição fitoquímica e doseamento de flavonoides totais dos extratos hidroalcoólicos de Cyperus iria L. e Cyperus articulatus L. - José Jailson Lima Bezerra; Carlos Luiz da Silva; Arthur Luy Tavares Ferreira Borges; Ticiano Gomes do Nascimento; Ana Paula do Nascimento Prata (Universidade Estadual de Alagoas, 2018)
: In recent years, pharmacological research has evidenced the therapeutic potential of some species of the Cyperaceae Family. Thus, the present work was carried out with the objective of analyzing the phytochemical composition and determining the total flavonoids from the hydroalcoholic extracts of Cyperus iria L. and Cyperus articulatus L. The plant material was collected in Serra Dois Irmãos, Viçosa, Alagoas, in the month of January 2018 and the exsicates were deposited in the Herbarium of the Institute of the Environment of Alagoas (IE-AL). Subsequently, hydroalcoholic extracts were prepared based on the aerial parts (AP) and underground parts (UP) of the two species collected. From the sample obtained from the crude extracts of C. articulatus and C. iria, 35,0 ml were separated for phytochemical prospection. Total flavonoid content was determined using the 5% aluminum chloride (AlCl3) spectrophotometric method in methanol. The results concerning the phytochemical prospecting of extracts of the aerial and subterranean parts of C. iria and C. articulatus presented some chemical compounds, such as: phenols, flobafenic tannins, catechins, flavanones, flavonols, xanthones, flavononols and alkaloids. Regarding the dosage of total flavonoids, it was evidenced that the extracts of the PA have a higher flavonoid content than in the PS. Thus, it is suggested that new studies be conducted to evaluate the biological activities of the species studied.